PENGEMBANGAN MODUL AJAR BERBASIS INVENTARISASI TANAMAN SEKITAR PEMANDIAN ALAM UMBUL MARIAH BANDAR SIMALUNGUN SEBAGAI PENUNJANG MATERI KEANEKARAGAMAN HAYATI KELAS X SMA/MA - Kurniawati, Sherly; Rasyidah; Syarifah Widya Ulfa (STAI Nurul Falah Airmolek, 2025)
Abstract This study aims to determine whether the teaching module based on plant inventory as a support for biodiversity is feasible, practical, and effective in the learning process. This study uses the Research and Development (RnD) research method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The instruments used in this study were interview sheets, validation sheets for material experts, media experts, and questions, questionnaires for biology teacher responses and student responses and tests. The results of this study indicate that the teaching module based on plant inventory around the Umbul Mariah Bandar natural baths that has been developed has validity in the material aspect with a percentage of 97%, in the media aspect it has a percentage of 89.5%. The practicality module from the teacher response questionnaire obtained a percentage of 100% and the practicality of the student questionnaire obtained a percentage of 92.5%. The effectiveness of the posttest and pretest results obtained an N-Gain value of 0.87 with a percentage of 87.7%. With these results, the module is declared feasible to use. Thus, the module that is expected in the future can be used in future learning and research. Keywords: ADDIE, Inventory, Biodiversity, Module.